Single cell network profiling assay in bladder cancer - Covey, Todd M.; Vira, Manish A.; Westfall, Matt; Gulrajani, Michael; Cholankeril, Michelle; Okhunov, Zhamshid; Levey, Helen R.; Marimpietri, Carol; Hawtin, Rachael; Fields, Scott Z.; Cesano, Alessandra (Cytometry. Part A, 2013)
The aim of this study was to assess the feasibility of applying the single cell network profiling (SCNP) assay to the examination of signaling networks in epithelial cancer cells, using bladder washings from 29 bladder cancer (BC) and 15 nonbladder cancer (NC) subjects. This report describes the methods we developed to detect rare epithelial cells (within the cells we collected from bladder washings), distinguish cancer cells from normal epithelial cells, and reproducibly quantify signaling within these low frequency cancer cells. Specifically, antibodies against CD45, cytokeratin, EpCAM, and cleaved‐PARP (cPARP) were used to differentiate nonapoptotic epithelial cells from leukocytes, while measurements of DNA content to determine aneuploidy (DAPI stain) allowed for distinction between tumor and normal epithelial cells. Signaling activity in the PI3K and MAPK pathways was assessed by measuring intracellular levels of p‐AKT and p‐ERK at baseline and in response to pathway modulation; 66% (N = 19) of BC samples and 27% (N = 4) of NC samples met the “evaluable” criteria, i.e., at least 400,000 total cells available upon sample receipt with >2% of cells showing an epithelial phenotype. The majority of epithelial cells detected in BC samples were nonapoptotic and all signaling data were generated from identified cPARP negative cells. In four of 19 BC samples but in none of the NC specimens, SCNP assay identified epithelial cancer cells with a quantifiable increase in epidermal growth factor‐induced p‐AKT and p‐ERK levels. Furthermore, preincubation with the PI3K inhibitor GDC‐0941 reduced or completely inhibited basal and epidermal growth factor‐induced p‐AKT but, as expected, had no effect on p‐ERK levels. This study demonstrates the feasibility of applying SCNP assay using multiparametric flow cytometry to the functional characterization of rare, bladder cancer cells collected from bladder washing. Following assay standardization, this method could potentially serve as a tool for disease characterization and drug development in bladder cancer and other solid tumors. © 2013 International Society for Advancement of Cytometry